If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (n + -2)(n + -1) = 0 Reorder the terms: (-2 + n)(n + -1) = 0 Reorder the terms: (-2 + n)(-1 + n) = 0 Multiply (-2 + n) * (-1 + n) (-2(-1 + n) + n(-1 + n)) = 0 ((-1 * -2 + n * -2) + n(-1 + n)) = 0 ((2 + -2n) + n(-1 + n)) = 0 (2 + -2n + (-1 * n + n * n)) = 0 (2 + -2n + (-1n + n2)) = 0 Combine like terms: -2n + -1n = -3n (2 + -3n + n2) = 0 Solving 2 + -3n + n2 = 0 Solving for variable 'n'. Factor a trinomial. (1 + -1n)(2 + -1n) = 0Subproblem 1
Set the factor '(1 + -1n)' equal to zero and attempt to solve: Simplifying 1 + -1n = 0 Solving 1 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1n = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1n = 0 + -1 -1n = 0 + -1 Combine like terms: 0 + -1 = -1 -1n = -1 Divide each side by '-1'. n = 1 Simplifying n = 1Subproblem 2
Set the factor '(2 + -1n)' equal to zero and attempt to solve: Simplifying 2 + -1n = 0 Solving 2 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1n = 0 + -2 -1n = 0 + -2 Combine like terms: 0 + -2 = -2 -1n = -2 Divide each side by '-1'. n = 2 Simplifying n = 2Solution
n = {1, 2}
| 3x^2-2x=81-2x-x^2 | | 5x+6=-99+10x | | (2r+1)(r-5)=0 | | 2=5x+1 | | 2x+28=10x-52 | | 5x+10=95+x | | (m-5)(3m+1)=0 | | 8-x=29 | | -3+5=5a | | 10(x-5)+25=10x-5(10-x) | | z^2+9=0 | | (2v-2)=0 | | 12a^2=-3 | | 4x^2=-3x | | [4-y]=1 | | 13=-3+2a | | 8+3x=x-2 | | 3x+13-73=3x | | 3x+30=15x-60 | | -1=-1+x | | -0.166t=9 | | 6d+5=3d+23 | | 3x(4+5)=4 | | 5.68+.81= | | 0.05=0.2x-10 | | 16(x-278)=6(x-8) | | -9=-2+2x | | -.75x=-4 | | 6(x^2+2x)=2 | | (5n-4)(n-1)=0 | | -7=2+8z | | 34=22-5x |